1977
DOI: 10.1139/v77-373
|View full text |Cite
|
Sign up to set email alerts
|

On the induced decomposition of α-phenylethylhydroperoxide by peroxy radicals

Abstract: The induced decomposition of α-phenylethylhydroperoxide (HROOH) has been investigated in three different systems: hydroperoxide + cyclohexene + AIBN + O2 (I); cyclohexene substituted by isooctane (II), and cyclohexene substituted by chlorobenzene (III). The decomposition products of the HROOH were in all cases acetophenone (RO) and methylphenylcarbinol (HROH).It was established that peroxy radicals induced the decomposition. The considerable material balance deficit in I is due to the addition of the peroxy ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

1989
1989
1994
1994

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…The temperature dependence of the reaction between 1-phenylethyl peroxy radicals and 1-phenyl ethanol is in very good agreement with the data of Hajdu et al [6], and they seem to be in reasonable agreement with k = 80 M--' s-' measured at T = 120°C by Danoczy et al [4] using indirect mehods. This work was supported by the OTKA grant No.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The temperature dependence of the reaction between 1-phenylethyl peroxy radicals and 1-phenyl ethanol is in very good agreement with the data of Hajdu et al [6], and they seem to be in reasonable agreement with k = 80 M--' s-' measured at T = 120°C by Danoczy et al [4] using indirect mehods. This work was supported by the OTKA grant No.…”
Section: Discussionsupporting
confidence: 90%
“…Results are given in Table 3. Taking into consideration also the data of Hajdu et al [ 6 ] , the Arrhenius plot is shown in Fig. 4…”
Section: C-h Bond Activated By A-oh Group Further Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…(lo)] or via reactions [eqns. (12), ( 13) and ( 14)]. A less likely process for ketone formation would be the heterolytic decomposition of alkyl hydroperoxides [eqn.…”
mentioning
confidence: 99%
“…Dean and Skirrow I241 suggested, on the other hand, that the radical RO; triggers the decomposition of hydroperoxide, giving rise to the appearance of an alcohol through a reaction proceeding via formation of an intermediate complex[25] :…”
mentioning
confidence: 99%